The Typology of The Global Financial Crisis and the Solution in Islamic Economic Perspective - Ramdansyah Fitrah; Ridha Alhamdi; M. Shabri Abd. Majid; Marliyah, Marliyah,; Rita Handayani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Economic globalization has triggered more frequent financial crises. Financial crises constantly repeat every specific time. This article reviews the typology of the global financial crisis and the solutions offered by Islamic economics. The research uses a historical approach. Five typologies of the global financial crisis, namely: Speculative bubbles and Crash, Sovereign Default, Balance of payment crisis, systemic banking crisis, and Energy Crisis. The financial crisis typologies of Speculative bubbles and Crash are the Wall Street Crash of 1929 and the Great Depression, Black Monday, Japanese Asset Bubble, Dot-com Bubble, US Saving & Loan Crisis, and the Suprime Mortgage Crisis. The financial crisis typology of Sovereign Default is the Latin American Debt Crisis, the Mexican Peso Crisis, the Asian Financial Crisis, and the European Crisis. The typology of financial crisis Balance of payment crisis is the Mexican Peso Crisis and the Russian Financial Crisis. The financial typology of the energy crisis is the oil crisis. Islamic economics offers a solution so that the financial crisis does not recur in the future. The prohibition of riba, maysir and ghaarar transactions offers a solution to the financial crisis typology of Speculative bubbles and Crash. The principle of equity financing in Islamic economics is a solution to the financial crisis of the Sovereign Default typology. Islamic economics prioritizes the financial sector, which is in line with the real sector as a solution to the financial crisis typology of the Balance of payment crisis. The value of morality (akhlakul karimah) is a solution to the financial crisis because of the moral hazard.